Співець і культурний ідентитет - Сувайджич, Б. (Народна творчість та етнологія, 2012)
The paper deals with the bard of oral epic poetry as a carrier of collective memory in the context of cultural identity development in the community. This identity is based on the maturation process of integrating social factors in a particular historical moment. The bard is a representative of the social attitudes in the community, an archivist of collective memory, which is stored in the motif flows retrieved from the tradition in the specific poetics of epic poetry, a metaphorical holder of the oral knowledge. Due to his activity in the collective, he becomes «a cultural type» in the process of oral communication, a specific «social institution» of oral culture.